Preparation and Surface Analysis of Ultrathin Photoresist for Microlithography - Mohamed, Norani Muti; Kin Yin, Chee (Malaysian Journal of Science, 2002)
In integrated circuit (IC) technology the demand for faster and increased memory storage capacity has led to a continuous refinement of microlithograhic techniques for producing smaller circuit elements. Thus this requires submicron resolution which necessitates a move from conventional photolithography to techniques involving X-rays, and electron or ion beams. The ultrathin film of Ãâ€°-tricosenoic acid (30 Ã¢â‚¬â€ 1000Ãƒâ€¦) obtained by LB technique has been reported to have acceptable resolution, sensitivity and contrast to produce very small feature sizes. These monomolecular photoresists have found the application in the area of electron beam lithography. Here, the study focused on the preparation of these films in order to produce a uniform and controllable thickness of films suitable for high-resolution electron beam irradiation. Surface analysis of the films have shown that besides other factors such as type of deposition, temperature of the water subphase, speed of the barriers, the degree of adherence of Langmuir film to different substrates could also be detrimental to the film quality.